Combination of Minimum-Maximum (m-m) Attribute and Zero-INTENS-Difference (z-i-d) Attribute for Estimating Seismically Thin-Bed Thickness - Eko Widi Purnomo; Zuhar Zahir Tuan Harith (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
This paper demonstrates a new alternative way in estimating seismically thin-bed (below-tuning) thickness. Initial thickness is built by bandpass filtering the amplitude display of a zero-phase seismic. The filter removes the non minimum and or non maximum and left the maximum and or the minimum of seismic amplitude. The unresolved below-tuning thickness is then corrected by zero-INTENS-difference (z-i-d) attribute. INTENS is integrated energy spectra, an attribute which can be derived from spectral analysis. z-i-d attribute is zero difference of INTENS between the seismic and its synthetic. The method generates INTENS difference profile by subtracting seismic INTENS and its synthetic INTENS iteratively. The iteration is controlled by dipole space shifting from distance to closer or vice versa. The true thickness is derived by locating z-i-d which laid in INTENS different profile. It has found that, for free noise true seismic and perfect-wavelet (a wavelet which only approximately similar with wavelet which constructing the true seismic) synthetic seismic, in INTENS different profile, the z-i-d location always corresponds to true dipole space or thickness. The method could resolve all thickness of a wedge-modeled seismic with three different dominant frequencies. When the synthetic seismic is constructed with imperfect wavelet, slightly different analysis is needed to locate z-i-d attribute and the result is not as perfect as when perfect wavelet constructing synthetic seismic. A quiet similar result is got when the method is implemented for noisy wedge-modeled seismic. Bad thickness estimation is resulted for 20% noise seismic. The method algorithm is extended for similar dipole polarity model and multilayer model to bring the method to real seismic data nearer. The extension is done by estimating thickness of every layer of a stacked-wedge-modeled seismic. The algorithm then generalized for estimating layers thickness with several thickness combinations. The method was able to delineate shallow channel of Stratton Field by providing good pseudo-acousticimpedance (pseudo AI) map.